A Case Study Using Seismic Reflection and Well Logs to Reduce and Quantify Uncertainty During a Hydrogeological Assessment - Claprood, Maxime; Gloaguen, Erwan; Béraud, Thomas; Blouin, Martin; Dupuis, Christian; Ferron, Philippe; Ouellet, Michel; Chaussé, Michel; Martel, Richard; Paradis, Daniel; Ballard, Jean-Marc (Frontiers in Water, 2022)
Building a representative tri-dimensional conceptual model of the hydrostratigraphic units is the critical first step when undertaking a hydrogeological assessment. The construction of such conceptual model requires integrating all geological data available for reducing the uncertainty of the conceptual model. In addition, the different types of data collected do not have the same level of uncertainty, and this has to be considered during the modelling. This manuscript presents a geostatistical workflow developed to integrate high resolution seismic reflection data with geological well markers and well logs. The proposed workflow allows reducing and quantifying the uncertainty when developing the conceptual model of hydrostratigraphic units and estimating the spatial distribution of hydraulic conductivity needed to simulate groundwater flow. The study involves the field investigation and numerical modelling for understanding the hydraulic connection between a local sand and gravel esker aquifer overlying a fractured bedrock regional aquifer. Seismic reflection data recorded in 2019 and 2021 significantly modify the conceptual model originally envisioned at site by discovering unknown deep esker extensions. Seismic data also help reducing the spatial uncertainty by delimiting the lateral extents, thickness, and depth of the esker aquifer between existing boreholes. Thickness maps of major hydrostratigraphic units are computed by first interpolating the data with higher uncertainty, which are then locally deformed by successive kriging with external drift to honour data with lower uncertainty. Well logs are then used to link seismic with hydraulic parameters of hydrostratigraphic units, quantifying the uncertainty on hydraulic parameters and its spatial distribution. These modifications in the conceptual model of hydrostratigraphic units and the better understanding of the vertical heterogeneity of the hydraulic conductivity significantly impact the simulation of groundwater flow, both regionally and locally at site.